Recovery of Ammonia in Raw and Co-digested Swine Manure Using Gas-Permeable Membrane Technology - Oliveira Filho, Jose de Souza; Daguerre-Martini, Silvana; Vanotti, Matias B.; Saez-Tovar, Jose; Rosal, Antonio; Perez-Murcia, Maria D.; Bustamante, Maria A.; Moral, Raul (Frontiers in Sustainable Food Systems, 2018)
Anaerobic digestion of agro-industrial and livestock waste generates considerable digestate volumes that are important sources of nitrogen (N). However, on some occasions, the high concentrations of N present in the digestates may represent an obstacle to its use locally as fertilizer, since it can cause an environmental impact (EC, 2000). This study analyzes the efficiency of gas-permeable membranes (GPM) in the recovery of the ammoniacal nitrogen (NH4+) present in the swine manure (SM, Control) and three digestates generated from the anaerobic co-digestion of mixtures of SM, fruit and vegetable sludge (FVS) from the vegetable industry (peppers and artichokes), and by-products of the tomato processing industry (TW) (skins and seeds), which were mixed at three different proportions [TW + FVS]: [SM]. Their NHx+ content was 2,240 mg L-1 for the SM and 4,670 to 5,370 for the digestate mixtures. Throughout the duration of the Necovery experiment (96 hours), the percentages of NH4+ removal and recovery achieved were consistent among treatments, approximatelly 78% and 96%, respectively. The recovery of NH4+ for the digestate mixtures seems to be dependent on the treatment time, since the potential of N recovery was higher when the treatment time increased. However, for the control experiment (SM), with lower N concentration, the maximum N recovery was obtained at the experimental time established, without increasing the treatment time.